A Novel Subfamily GH13_46 of the α-Amylase Family GH13 Represented by the Cyclomaltodextrinase from Flavobacterium sp. No. 92 - Filip Mareček; Štefan Janeček (Molecules, 2022)
In the CAZy database, the α-amylase family GH13 has already been divided into 45 subfamilies, with additional subfamilies still emerging. The presented in silico study was undertaken in an effort to propose a novel GH13 subfamily represented by the experimentally characterized cyclomaltodxtrinase from Flavobacterium sp. No. 92. Although most cyclomaltodextrinases have been classified in the subfamily GH13_20. This one has not been assigned any GH13 subfamily as yet. It possesses a non-specified immunoglobulin-like domain at its N-terminus mimicking a starch-binding domain (SBD) and the segment MPDLN in its fifth conserved sequence region (CSR) typical, however, for the subfamily GH13_36. The searches through sequence databases resulted in collecting a group of 108 homologs forming a convincing cluster in the evolutionary tree, well separated from all remaining GH13 subfamilies. The members of the newly proposed subfamily share a few exclusive sequence features, such as the “aromatic” end of the CSR-II consisting of two well-conserved tyrosines with either glycine, serine, or proline in the middle or a glutamic acid succeeding the catalytic proton donor in the CSR-III. Concerning the domain N of the representative cyclomaltodextrinase, docking trials with α-, β- and γ-cyclodextrins have indicated it may represent a new type of SBD. This new GH13 subfamily has been assigned the number GH13_46.